2018
DOI: 10.1002/cam4.1658
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inhibitors of apoptosis proteins suppresses medulloblastoma cell proliferation via G2/M phase arrest and attenuated neddylation of p21

Abstract: Medulloblastoma (MB) is the most common type of malignant childhood brain tumor. We previously showed that inhibitors of apoptosis proteins (IAP) small‐molecule inhibitors (LCL161 or LBW242) combined with chemotherapy have synergistic antiproliferative effects on MB cells. The synergistic antitumor effects of combination treatments happen through induction of autophagy and caspase‐3/7‐activated apoptosis. Here, we investigated the effects of IAP inhibitors or silencing IAP on cell cycle regulation. We discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The impact of LCL/LBH exposure on proteins involved in the canonical NF-κB pathway was examined. Exposure (16 or 24 hr) of U266 or MM.1S to LCL (± LBH) markedly downregulated cIAP1 as previously described in multiple other cell types [19][20][21] but had a more modest effect on cIAP2 (Figure 2A and 2B, upper panels). Co-treatment also sharply induced γH2A.X, an indicator of DNA damage known to be induced by Smac-mimetics, 22 in both MM cell lines (Figure 2A and 2B, upper panels).…”
Section: The Combination Of Lcl161 and Lbh589 Down-regulates Ciap1 Induces γH2ax But Does Not Inactivate The Canonical Nf-b Pathway In MMsupporting
confidence: 79%
“…The impact of LCL/LBH exposure on proteins involved in the canonical NF-κB pathway was examined. Exposure (16 or 24 hr) of U266 or MM.1S to LCL (± LBH) markedly downregulated cIAP1 as previously described in multiple other cell types [19][20][21] but had a more modest effect on cIAP2 (Figure 2A and 2B, upper panels). Co-treatment also sharply induced γH2A.X, an indicator of DNA damage known to be induced by Smac-mimetics, 22 in both MM cell lines (Figure 2A and 2B, upper panels).…”
Section: The Combination Of Lcl161 and Lbh589 Down-regulates Ciap1 Induces γH2ax But Does Not Inactivate The Canonical Nf-b Pathway In MMsupporting
confidence: 79%
“…For example, IAPs disrupted chromosomal passenger complex (CPC) localization to the centromeres and interacted with the serine/threonine-protein kinase polo, indicating that iaps were involved in regulation of the cell cycle [52,53]. In medulloblastoma cells, ciap1/2 or xiap regulated G2/M phase progression via Cyclin B1-CDK1 and Cyclin A-CDK1/2 [71]. The treatment of human laryngeal carcinoma cells with Xiap-shRNA induced G0/G1 phase arrest [72].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on patients with advanced solid tumors involving cotreatment with LCL161 and paclitaxel, as well as cotreatments with other chemotherapeutic agents, are ongoing [23,25]. Notably, studies have reported that a combination of LCL161 with cisplatin, vincristine, or immune checkpoint inhibitors produced the highest antitumor activity in cancer cells [26][27][28]. The combination of LCL161 with topotecan was tested for ovarian cancer [23]; however, this combination has yet to be tested for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%